Photodisintegration of H-3 in a three dimensional faddeev approach - Bayegan, S.; Shalchi, M. A.; Hadizadeh, M. R. [UNESP]; Eplelbaum, E.; Hammer, H. W.; Meibner, U. G. (E D P Sciences, 2009)
An interaction of a photon with H-3 is invstigated based on a three dimensional Faddeev approach. In this approach the three-nucleon Faddeev equations with two-nucleon interactions are formulated with consideration of the magnitude of the vector Jacobi momenta and the angle between them with the inclusion of the spin-isospin quantum numbers, without employing a partial wave decomposition. In this formulation the two body t-matrices and triton wave function are calculated in the three dimensional approach using AV18 potential. In the first step we use the standard single nucleon current in this article.